PENYULUHAN PENGGUNAAN SISTEM E-COURT DI PENGADILAN NEGERI INDRAMAYU - Abdur Rahim; Fajar Hidayat; Umar Hadid; Warto Warto (LPPM Universitas Bina Bangsa, 2023)
One of these innovative systems is called the Supreme Court Innovation System E-Court when facing challenges related to the development of human life, which is regulated in the Republic of Indonesia Supreme Court Laws and Regulations No. 1 of 2019 the use of electronics. Handling cases and proceedings in court. This system was created to overcome Indonesia's geographical boundaries. Alignment of the legal system with existing principles and public trust in law enforcement will be strengthened. The justice system applies law and justice. Implementation method with the planning and implementation stages. Application of assisted law-seeking electronic courts, including legal instruments, to create judicial effectiveness and efficiency